Rural development in Eurasia and the Middle East : land reform, demographic change, and environmental constraints - Engelmann, Kurt; Pavlaković, Vjeran (Russian, East European, and Central Asian Studies Center, Henry M. Jackson School of International Studies, University of Washington in association with University of Washington Press, 2001)
"The ties that bind Central Asia to the Middle East have increased dramatically in recent years, as political emancipation from Soviet rule has spurred the restoration of material culture shared by Turkic and Iranian peoples. Political institutions and farming practices, however, are still based on the Soviet model, with centralised large-scale agricultural production serving Russian rather than local needs. The contributors to this volume examine land reform and agricultural development in Russia, Central Asia, North Africa, and the Middle East. Their studies bring into question the evolutionary view of agricultural development, from small-scale subsistence to large-scale commercialised agricultural systems, and emphasise the need to understand the specific political, historical, and geographic contexts of rural development and land reform. This volume is a must for regional specialists, historians, economists, and those working on rural development issues throughout Eurasia."